The Friction of Saline Ice on Aluminium. (18th April 2016) - Wallen-Russell, Christopher; Lishman, Ben
Abstract : The friction of ice on other materials controls loading on offshore structures and vessels in the Arctic. However, ice friction is complicated, because ice in nature exists near to its melting point. Frictional heating can cause local softening and perhaps melting and lubrication, thus affecting the friction and creating a feedback loop. Ice friction is therefore likely to depend on sliding speed and sliding history, as well as bulk temperature. The roughness of the sliding materials may also affect the friction. Here we present results of a series of laboratory experiments, sliding saline ice on aluminium, and controlling for roughness and temperature. We find that the friction of saline ice on aluminiumμ ice-al = 0.1 typically, but that this value varies with sliding conditions. We propose physical models which explain the variations in sliding friction.